The emerging role of extracellular vesicles in diabetes and complications: mechanistic insights and translational prospects - Liu, Siyuan; Pan, Zhicheng; Chen, Xuzhuo; Wang, Zhenlin; Zhong, Wei; Ling, Jitao; Chen, Yixuan; Xia, Panpan; Zhang, Deju; Liu, Xiao; Yu, Peng; Hu, Zhen; et al. (Frontiers in Endocrinology, 2025)
Extracellular vesicles (EVs), particularly exosomes, have emerged as key players in diabetes pathogenesis, diagnosis, and therapy. They regulate intercellular communication, influence islet function, and contribute to diabetic complications such as retinopathy, nephropathy, and cardiomyopathy. Their potential as liquid biopsy biomarkers and engineered therapeutic carriers—delivering nucleic acids, proteins, or stem cell-derived regenerative signals—offers promising avenues for diabetes management. However, there are some critical challenges in clinical translation. Future research must prioritize (1) scalable GMP-compliant production with rigorous quality control, (2) targeted delivery systems via ligand modification or biomimetic engineering, (3) improved biocompatibility through cargo optimization and stealth coatings, and (4) large-scale clinical trials to validate efficacy and safety. Addressing these hurdles is essential to harness EVs’ full potential and accelerate their transition into mainstream diabetic care.